Piezosurgery - A Safe Technique to Perform Lateral Suboccipital Craniotomy? - Grauvogel, Juergen; Masalha, Waseem; Heiland, Dieter Henrik; Jarc, Nadja; Grauvogel, Tanja Daniela; Scheiwe, Christian (Operative Neurosurgery, 2018)
BACKGROUND Piezosurgery (PS) is a relatively new technique based on microvibrations generated by the piezoelectric effect. It selectively cuts bone tissue and preserves the surrounding soft tissue. OBJECTIVE To evaluate the use of PS for performing lateral suboccipital craniotomy. METHODS PS was used to perform a lateral suboccipital craniotomy in 22 patients who underwent surgery for different cerebellopontine angle (CPA) pathologies in the neurosurgical department. The applicability of PS for lateral suboccipital craniotomy was evaluated with respect to safety, preciseness of bone cutting, and in particular the preservation of the adjacent dura and sigmoid and transverse sinuses. RESULTS Lateral suboccipital craniotomy in 22 patients who underwent surgery for different CPA pathologies (13 vestibular schwannoma, 5 petrous bone meningioma, 1 petroclival meningioma, 2 epidermoid cysts, and 1 petrous bone cholesterol granuloma) was performed with PS without any complications. A burr hole was set before piezosurgical craniotomy in 6 patients, with no prior burr hole in 16 patients. Incidental durotomy during piezosurgical craniotomy occurred in 6 patients, and small lacerations of the sigmoid sinus caused by the piezosurgical device were observed in 3 patients. CONCLUSION Although PS is a safe and selective bone cutting technique that preserves the surrounding soft tissue, it can still lead to unintended dural tears during lateral suboccipital craniotomy. This must be kept in mind when using PS for craniotomies and relying on the selective bone cutting properties of PS.
CRIS-Team Scopus Importer:2024-03-07
Keywords: Cerebellopontine angle surgery; Lateral suboccipital craniotomy; Piezoelectric bone surgery; Piezosurgery